Employment stability in newly founded firms: a matching approach using linked employer-employee data from Germany - Schnabel, Claus; Kohaut, Susanne; Brixy, Udo (Small Business Economics, 2011)
Using a linked employer-employee dataset and taking the perspective of individuals rather than firms, this paper analyzes some effects of joining startups. We show that entrants in new firms differ from those joining incumbent firms, and we use a matching approach to compare a group of employees joining new firms in 1995/1996 with a control group entering incumbent firms. Our results indicate that individuals' employment stability was higher in incumbent than in newly founded firms, while their risk of becoming unemployed was lower. In particular in eastern Germany, joining firms that were older than 6 years improved individuals' employment prospects. © 2009 Springer Science+Business Media, LL
WiSo-Import:2015-03-26:1703
Keywords: Employment; Germany; Linked employer-employee data; Newly founded firms; Unemployment